ANALISIS KUALITAS PELAYANAN PT KAI (KERETA EKONOMI) DAOP IV SEMARANG SEBAGAI TRANSPORTASI PUBLIK - Stefanus Sonny Prasetyo; Endang Larasati; Dyah Hariani (Journal of Public Policy and Management Review, 2015)
Quality of service is one measure to assess the public service. Transportation services is one of the basic services organized a public organization. PT KAI DAOP (operational area) IV Semarang is a public organization which organizes transportation services in Indonesia. One of the products of services provided by PT KAI is the economy-class train. Economy-class train passengers assessed can help lower classes because the price is relatively cheaper. To be able to know the quality of services provided by PT KAI Daop IV Semarang to train users economy can be seen from the five aspects, namely tangible, reliability, responsiveness, assurance, empathy. Researchers conducted interviews, field observations and literature to identify the quality of services performed by PT KAI Daop IV Semarang to the economic train passengers. Indicators studied were the facilities, the appearance of officers, service personnel, readiness officer, the impression of the service provider, the response personnel, trust in travel, safety and passenger comfort, the attention of officers and justice officials. The overall study results is the quality of services performed by PT KAI Daop IV Semarang against economic train passengers has been good enough, but there are still some aspects that must be considered and corrected, such as facilities, response officers and justice officials.